Examining Political Satire in Indonesian TikTok Videos: An Analysis of Humor and Commentary - Nugraha, Danang Satria (Language Circle: Journal of Language and Literature, 2025)
This study delves into the use of satirical comments and political humor in TikTok videos in Indonesia, utilizing a critical discourse analysis (CDA) framework. The study aims to investigate how political issues and figures are depicted through satirical comments in society of the digital natives. The analysis focused on TikTok users’ linguistic and discursive strategies to criticize and satirize political events, figures, and policies. The study used a collection of TikTok videos. It employed a multi-modal approach, analyzing the textual content and visual and audio elements contributing to humor and satire. A qualitative methodology combining content analysis with discourse analysis techniques was used to identify recurring themes, rhetorical devices, and humor patterns in the satirical comments. Specifically, the application of CDA facilitated the deconstruction of power dynamics embedded within the satirical discourse, revealing how TikTok users leverage humor to challenge dominant political narratives. The findings revealed that TikTok users used linguistic devices such as irony, sarcasm, parody, and wordplay to convey their satirical messages. The satirical comments often targeted political figures, policies, and events, focusing on corruption, governance, and social inequality issues. Through humor, TikTok users expressed their dissent and critique of the political system while also participating in creating an alternative public sphere for political discourse. However, the study noted that these satirical comments could be controversial, as they may perpetuate stereotypes or reinforce existing political biases.